PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DI PT TIGA SERANGKAI PUSTAKA MANDIRI SURAKARTA - -, Praptiestrini (Universitas Slamet Riyadi, 2015)
This research examined the influence of corporate culture on job performance of PT. Tiga Serangkai Pustaka Mandiri Surakarta. The variables consist of corporate culture and job performance. The corporate culture variables consists of six indicators, the are: (1) Innovation, (2) Outcome orientation, (3) People orientation, (4) Team orientation, (5) aggressiveness; (6) Stability. Job performance consists of (1) quality, (2), quantity, and (3) time. Data were analyzed with SEM. This research is descriptive and explanatory research survey. This study took a sample of 173 respondents, employees of PT.Tiga Serangkai Pustaka Mandiri Surakarta, with random sampling. The results show that: factors: Innovation, Outcome orientation, People orientation, Team orientation, aggressivess, stability, contribution significant to support corporate cultural factors in the PT. Tiga Serangkai Pustaka Mandiri Surakarta. Factors: the quantity, quality, and time has contribution to the job performance of PT. Tiga Serangkai Pustaka Mandiri Surakarta. Time variables contributed dominant compared with other factors. PT. Tiga Serangkai Pustaka Mandiri Surakarta corporate culture, affect the Job performance of PT. Tiga Serangkai Pustaka Mandiri Surakarta. The values are determined by the corporate culture of innovation, outcome orientation, people orientation, team orientation, aggressiveness, stability as a character has shaped the culture as the main of PT. Tiga Serangkai Pustaka Mandiri Surakarta. Keywords: Corporate Culture, Job Performance.